Food literacy and diet quality in young vegans, lacto-ovo vegetarians, pescatarians, flexitarians and omnivores - Synne Groufh-Jacobsen; Christel Larsson; Wim Van Daele; Claire Margerison; Isabelle Mulkerrins; Lale Marie Aasland; Anine Christine Medin (Cambridge University Press, 2023)
Abstract Objective: To investigate whether food literacy competencies and diet quality vary between 16-to-24-year-olds vegans, lacto-ovo vegetarians, pescatarians, flexitarians and omnivores and to assess whether food literacy is associated with diet quality. Design: Cross-sectional study. Food literacy (general nutrition knowledge, critical nutrition literacy and food skills) and diet quality were measured using an electronic questionnaire. Setting: Southern Norway, September 2021 - March 2022. Participants: Healthy 16-24-year-olds (n 165). Results: Overall, the mean general nutrition knowledge score was moderate (48·0 out of 67·0); the lowest mean score was found in omnivores and the highest in flexitarians (45·6 v. 51·5) (P = 0·034). The mean score of critical nutrition literacy was also moderate (3·7 out of 5·0); vegans showed higher scores compared to other dietary practices (P = 0·018). No difference was observed in food skills between the different dietary practices. The overall median diet quality score was 46·0 out of 80·0, lowest in omnivores and highest in vegans (42·0 v. 56·0) (P =< 0·001). In multivariate regression analyses, general nutrition knowledge, food skills and vegan dietary practice were significantly associated with higher diet quality. Conclusions: We found moderate levels of food literacy across all dietary practices. The food literacy competencies, general nutrition knowledge and food skills were associated with higher diet quality in our sample. Omnivores showed both the lowest general nutrition knowledge level and lowest diet quality scores. In contrast, both flexitarians and vegans scored highest on general nutrition knowledge and diet quality scores, despite being one of the less restrictive and one of the strictest plant-based dietary practices, respectively.